Pengaruh financial literacy, financial technology, dan entrepreneurial orientation terhadap kinerja UMKM - Zidni Thoriqul Jannah (Universitas Negeri Surabaya, 2025)
This research aims to investigate the impact of financial literacy, financial technology, and entrepreneurial orientation on the performance of MSMEs in Mojokerto, East Java. The type of data used is quantitative data sourced from primary data. The population of this research is all MSMEs in Mojokerto, East Java. The sample retrieval technique used in this research involved saturated samples, yielding 61 MSMEs as samples. We analysed the data using logistic regression and calculated the results using IBM SPSS 26. The research results show that financial literacy, financial technology, and entrepreneurial orientation do not have a significant impact on MSMEs. Therefore, becoming a successful entrepreneur is not easy; starting is easy, but surviving requires considerable effort and sacrifice. The success of an entrepreneur lies in one's own mindset. The main requirement for success in business is to have a positive mindset, as it can provide strong motivation to achieve for those who don't give up easily.